Diet Diversity Through the Life-Course as an Opportunity Toward Food Allergy Prevention - Spolidoro, Giulia C. I.; Azzolino, Domenico; Cesari, Matteo; Agostoni, Carlo (Frontiers in Allergy, 2021)
The prevalence of food allergies (FA) is increasing worldwide. Generally, the onset of allergies, including FA, begins in early childhood and may persist and/or develop through the life-course. Even though epidemiological studies have focused mainly on children, allergies can also occur for the first-time during adulthood. Within the prolongation of life, it is expected that allergies will be encountered more often even in older people. Recent findings suggest that an early exposure to diverse food antigens may promote the development of immune tolerance. Accordingly, diet diversity during the first year of life or even earlier may have a positive impact on the prevention of allergies. The anti-inflammatory properties of some dietary nutrients may positively contribute to a tolerogenic immune environment too. Diet diversity is associated with a more favorable microbiome, and increasing evidence suggests a promising role of gut microbiota manipulation in inducing immune tolerance. Unjustified avoidance of allergenic foods may expose to intakes of some nutrients below recommended levels through the life-course, even more in cases of self-diagnosis and treatment of presumed forms of food intolerance. Nutritional strategies including the early exposure to a variety of food antigens are a promising area of research for preventive purposes through the life-course possibly extending positive outcomes to older stages. The aim of this paper is to highlight the role of diet diversity in preventing the development of FA starting in early life, as well as to provide an overview of the main strategies to prevent related nutritional issues throughout the life-course.